2022
DOI: 10.1007/s12144-022-03154-3
|View full text |Cite
|
Sign up to set email alerts
|

Belief in the importance of socially responsible behaviors – the significance of trust and personal experiences with Covid-19

Abstract: A vast number of studies have shown that trust is related to socially desirable traits and behaviors. In the present research we have investigated the relationship between generalized trust and beliefs about the importance of socially responsible behaviors (SRB) during the pandemic – namely, following the sanitary regime and getting vaccinated. Basing on the previous findings we assumed that trustful people would be more convinced of the benefits of complying with the pandemic restrictions and getting vaccinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Yet, more direct evidence further illuminates the role of indirect experience. Jasielska et al (2022) measured participants' indirect experiences (e.g., having a loved one who was infected by COVID‐19) as a correlate of PHBs, and in line with the findings from Dryhurst et al (2020), found these experiences to be positively associated with PHB compliance. Simply experiencing the virus—or knowing someone who has experienced the virus—firsthand seems to be an important factor in predicting both risk perception and, consequently, PHBs.…”
Section: Introductionmentioning
confidence: 79%
“…Yet, more direct evidence further illuminates the role of indirect experience. Jasielska et al (2022) measured participants' indirect experiences (e.g., having a loved one who was infected by COVID‐19) as a correlate of PHBs, and in line with the findings from Dryhurst et al (2020), found these experiences to be positively associated with PHB compliance. Simply experiencing the virus—or knowing someone who has experienced the virus—firsthand seems to be an important factor in predicting both risk perception and, consequently, PHBs.…”
Section: Introductionmentioning
confidence: 79%
“…In future studies, it would be advisable to add control questions to make sure that participants are actually attentive to the material (such as self-report indicators, bogus items, and instructed items; DeSimone & Harms, 2018). While studies on data from panels are gaining popularity (Federico et al, 2021;Jasielska et al, 2022;Zagefka, 2021), it is important to note the specificity of this form of recruitment. It would be advisable to replicate these results in other cultures, including countries with different characteristics on cultural dimensions (Hofstede et al, 2010), to check whether the ASI-R scale is culturally sensitive.…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…Indeed, both acute and chronic stressors impair the ability to assess the credibility of information, leading to a state of negative attention bias (Beck, 2005;Lenow et al, 2018). This carries troubling implications for not only future public health crises where cooperation with others will be paramount (Jasielska et al, 2023;J. Min, 2020;Sarracino et al, 2022;Yuan et al, 2022) but also for people's social interactions and relationships.…”
Section: Stress and Stress Mindset On Trustmentioning
confidence: 99%